SWK-06. ANSWERING 900 VOICES: A NATIONAL NONPROFIT ORGANIZATION RESPONDS TO A NATIONWIDE COMMUNITY HEALTH NEEDS ASSESSMENT THAT ELUCIDATED KEY CHALLENGES FACED BY PEDIATRIC BRAIN TUMOR FAMILIES. (4th December 2020) - Riley, Kathy
Abstract: The five-year relative survival rate for childhood primary brain and other central nervous system tumors is nearly 75 percent (Central Brain Tumor Registry of the United States, 2017). Nevertheless, childhood brain tumor survivors often suffer from lifelong side effects caused by their illness or treatments such as surgery, radiation and chemotherapy. To define the nature and extent of problems survivors and their families face, the Pediatric Brain Tumor Foundation (PBTF), the world's largest nonprofit solely dedicated to children and teens with brain tumors, conducted a 2017 national community health needs assessment in collaboration with the Sol Price Center for Social Innovation at the University of Southern California. The assessment found that pediatric brain tumor patients and their families face key challenges in four general areas: 1) interpersonal and emotional support, 2) logistical and financial support, 3) information and medical education gathering, and 4) educational and vocational anxieties. In 2020, the PBTF's response to the 900 assessment participants who represent the thousands living with the effects of this disease includes the launch of a national Peer to Peer Mentoring program to meet the ongoing challenges families face; the disbursement of emergency financial assistance to hundreds of families in the throes of treatment; and the distribution of a resource notebook for newly diagnosed families and a comprehensive guidebook for survivors and their families. The results of the needs assessment suggest additional clear, actionable areas for impact not only by the PBTF but by medical professionals, other nonprofit organizations and governmental agencies.